The Factors Associated with Nomophobia Among Bachelor of Nursing Students at Universitas Muhammadiyah Purwokerto - Khanani Azzahroh; Rakhmat Susilo (UM Purwokerto Press, 2024)
Background: Mobile phones have become essential tools for students due to their ability to meet various educational demands and provide access to a wealth of information. Excessive use and dependence on smartphones have also led to a new problem known as nomophobia. Nomophobia is a term derived from the phrase